2014
DOI: 10.1080/15287394.2014.865582
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Stimulates Motor Impairment And Cerebellar Mercury Deposition in Methylmercury-Exposed Mice

Abstract: Methylmercury (MeHg) is a highly toxic environmental contaminant that produces neurological and developmental impairments in animals and humans. Although its neurotoxic properties have been widely reported, the molecular mechanisms by which MeHg enters the cells and exerts toxicity are not yet completely understood. Taking into account that MeHg is found mostly bound to sulfhydryl-containing molecules such as cysteine in the environment and based on the fact that the MeHg-cysteine complex (MeHg-S-Cys) can be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
3
3
0
Order By: Relevance
“…MeHg exposure significantly decreased the rat hippocampal TSH level and GR activity, while GST activity was significantly lower than that of the control group. This result was consistent with previous studies indicating that sulfhydryl groups represented the main target of MeHg in biological systems [ 34 ] and that MeHg decreased glutathione levels in the cerebellum [ 48 ]. This result was also consistent with a previous study showing that the CHCl 3 fraction of the Dendropanax morbifera methanol extract exerted protective effects through its antioxidant activity, protection of mitochondria, and anti-apoptotic actions [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…MeHg exposure significantly decreased the rat hippocampal TSH level and GR activity, while GST activity was significantly lower than that of the control group. This result was consistent with previous studies indicating that sulfhydryl groups represented the main target of MeHg in biological systems [ 34 ] and that MeHg decreased glutathione levels in the cerebellum [ 48 ]. This result was also consistent with a previous study showing that the CHCl 3 fraction of the Dendropanax morbifera methanol extract exerted protective effects through its antioxidant activity, protection of mitochondria, and anti-apoptotic actions [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Site-directed mutagenesis of LAT1 has been shown to cause a reduction in the cellular uptake of CH 3 Hg + , providing additional evidence for the hypothesis that CH 3 Hg- S -Cys is a substrate of LAT1 (Boado et al 2005). Taken together, these data provide strong support for the hypothesis that CH 3 Hg- S -Cys is taken into cells via one or both isoforms of System L. Interestingly, a recent study indicated that co-administration of methionine and CH 3 Hg + enhanced motor impairments in mice compared with administration of CH 3 Hg + alone (Zimmermann et al 2014). This finding suggests that a trans-stimulatory phenomenon may occur whereby the presence of additional substrate enhances the activity of the transporter so that more substrate, including CH 3 Hg + , is taken up by the carrier.…”
Section: Transport Of Methylmercurysupporting
confidence: 62%
“…The overproduction of ROS may trigger the cell to elevate antioxidants defenses in order to prevent cellular damage. Numerous studies demonstrated that neurons respond to MeHg exposure with enhanced ROS production, representing a key mechanism of cell damage Choi et al, 1996;Farina et al, 2011aFarina et al, , 2011bZimmermann et al, 2014), since the brain presents a highly susceptible tissue to oxidative stress due to its high rate of metabolism . In brain cells, Hg exposure modifies the physiological function of Figure 2.…”
Section: Discussionmentioning
confidence: 99%